1994
DOI: 10.1080/08824099409359936
|View full text |Cite
|
Sign up to set email alerts
|

Battered women's compliance‐gaining strategies as a function of argumentativeness and verbal aggression

Abstract: examined the types of verbally aggressive messages that abusive couples used prior to violent acts. Their findings suggest that violent couples use different messages than do nonviolent couples. Infante and his colleagues (1989) advanced an Argumentative Skills Deficiency Model of Interspousal Violence (ASD), which holds that husbands and wives involved in violent marriages are less argumentative and more verbally aggressive than nonviolent couples. Research indicates that message selection is, in part, a Junc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Coefficient alphas in this study were .87 (M = 23.47, SD = 7.66) for self verbal aggressiveness and .91 (M = 26.52, SD = 9.67) for sibling verbal aggressiveness. The means for verbal aggressiveness were consistent with previous research (Martin & Anderson, 1995a, 1996bRudd et al, 1994).…”
Section: Participantssupporting
confidence: 70%
See 1 more Smart Citation
“…Coefficient alphas in this study were .87 (M = 23.47, SD = 7.66) for self verbal aggressiveness and .91 (M = 26.52, SD = 9.67) for sibling verbal aggressiveness. The means for verbal aggressiveness were consistent with previous research (Martin & Anderson, 1995a, 1996bRudd et al, 1994).…”
Section: Participantssupporting
confidence: 70%
“…Previous studies have found this 10-item version to be reliable and valid Martin & Anderson, 1995b, 1996a, 1996bRudd, Burant, & Beatty, 1994). Items included: I attack the character of my sibling when attempting to influence him/her.…”
Section: Participantsmentioning
confidence: 99%
“…Others have reported reliability and validity for the 10-item version (Infante, Anderson, Martin, Herington, & Kim, 1993;Rudd, Burant, & Beatty, 1994). Reliability analysis of the 10-item, 5-point Likert-type, version produced a coefficient alpha of .82.…”
Section: Methodsmentioning
confidence: 97%
“…CONFLICT AND AGGRESSION 181 cock, Waltz, Jacobson, & Gottman, 1993;Sagrestano, Heavey, & Christensen, 1999), verbal aggression (Infante, Chandler, & Rudd, 1989;Infante, Sabourin, Rudd, & Shannon, 1990), and aggressive compliance gaining tactics (deTurck, 1987;Rudd, Beatty, & Burant, 1994).…”
mentioning
confidence: 99%